High-damping high-strength good-appearance polyamide composite material as well as preparation method and application thereof

By using raw materials such as PA6I and glass fiber in polyamide composite materials, combined with high-speed stirring and twin-screw extrusion technology, a high-damping and high-strength appearance polyamide composite material was prepared, which solved the shortcomings of the existing materials in both high-strength and high-damping temperature areas, and achieved efficient vibration damping and suspension effects around the automotive engine.

CN119875363APending Publication Date: 2025-04-25SHANGHAI PRET COMPOSITES +3
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411978045.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

Smart Images

  • Figure CN119875363A_ABST
    Figure CN119875363A_ABST
Patent Text Reader

Abstract

The invention discloses a high-damping, high-strength and good-appearance polyamide composite material and a preparation method thereof. The high-damping, high-strength and good-appearance polyamide composite material is prepared from the following raw materials in parts by weight: 30-60% of polyamide resin; 5 to 15% of semi-aromatic polyamide resin PA6I; 30 to 70% of glass fiber; 1-15% of an elastomer; 1-3% of a compatilizer; 0-1% of an antioxidant; 0-2% of a processing aid; and 0-1% of color master batch. The polyamide composite material has the advantages that by adding the PA6I, the damping effect of the polyamide composite material is improved, meanwhile, the appearance floating fiber of the high-glass-fiber-content filled polyamide composite material is greatly improved, and by adding the elastomer, the damping strength of the material is further improved. The high-damping, high-strength and good-appearance polyamide composite material prepared by the invention has important application prospects in vibration reduction and suspension systems around automobile engines, and a new material solution is provided for improving the NVH (Noise Vibration and Harshness) performance of automobiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymer materials, in particular to a high-damping, high-strength, good-appearance polyamide composite material and a preparation method thereof Background Art

[0002] With the development of scientific and technological innovation and modern industry, mechanical equipment tends to be faster, more integrated and simpler. The power of equipment increases and the number increases. The vibration, noise and fatigue failure problems caused by it are becoming more and more serious. The trend of using engineering plastics to replace some metal materials is becoming more and more obvious.

[0003] The basic principle of damping is energy loss. The mechanism of damping can be divided into four aspects according to the principle: internal friction of materials, external friction of materials, energy transmission and conversion, and conversion. The internal friction of materials is the mutual friction between the molecular segments inside the material to lose energy. The external friction of materials is the friction between two interfaces or the friction between the medium. The transmission and conversion of energy is the transmission of mechanical vibration energy inside the material and between the medium and the change of conversion into heat or electrical energy. Frequency conversion is the conversion of the frequency of mechanical vibration into another frequency to overcome the harm caused by mechanical vibration. At present, the most widely used and researched are polymer damping materials, which have significant viscoelasticity and a wide damping temperature range. The relevant technology is relatively mature in the rubber field, but the research in the field of engineering plastics is still in its infancy, especially in the application of glass fiber reinforced polyamide materials to replace the parts of the peripheral vibration reduction system of automobile engines.

[0004] Chinese patent CN114921091A discloses a glass fiber reinforced nylon composite material. By using a compound of polyamide resin and polyphenylene ether resin, and further adding maleic anhydride grafted elastomer and maleic anhydride grafted polyphenylene ether resin as compatibilizers and epoxy resin to enhance damping agents, a high damping glass fiber reinforced nylon composite material can be obtained. However, the injection molding appearance of the high glass fiber content filling material is relatively difficult to control the floating fiber. Chinese patent CN11840492A achieves that the filler in the polyamide composition can be enriched on the surface of the injection molded part by adding a low melting point polyamide resin in the formula and a customized processing technology. A good barrier effect can be achieved with a very small amount of addition, but it is only used to reduce the noise generated by the relative movement friction of the parts. CN115926364A discloses a long carbon chain nylon and ABS blend to improve the damping and noise reduction effect of the parts used in the range of 0-40℃, but the ABS addition content is high, which has a large loss in the mechanical properties of the nylon material. Summary of the invention

[0005] The present invention provides a high-damping, high-strength and good-appearance polyamide composite material, which has a higher damping temperature range while maintaining the high strength and good appearance of high-glass-fiber-content filled nylon, and can achieve the dual effects of strength and vibration and noise reduction in applications where plastic replaces steel.

[0006] The present invention is achieved through the following technical solutions:

[0007] A high-damping, high-strength, good-appearance polyamide composite material, comprising the following raw materials in parts by weight:

[0008] Polyamide resin 30-60%;

[0009] Semi-aromatic polyamide resin PA6I: 1-15%;

[0010] Glass fiber: 30-70%;

[0011] Elastomer: 1-15%;

[0012] Compatibilizer: 1-3%;

[0013] Antioxidant: 0-1%;

[0014] Processing aids: 0-2%;

[0015] Masterbatch: 0-1%.

[0016] The polyamide resin may be one or more of PA6, PA56, PA66, PA6 / 66, PA66 / 6, etc.;

[0017] The semi-aromatic polyamide resin PA6I is an amorphous polyamide resin, and its melting point glass transition temperature (Tg) is 120-130° C., and melt flow rate (MFR) is 25-40 g / 10 min (275° C., 2.16 kg);

[0018] The glass fiber is one or more of E glass fiber, S glass fiber, and A glass fiber.

[0019] The preferred glass fiber of the present invention is E glass, with an alkali content of less than 0.8%, a moisture content of ≤0.05%, and a bulk density of 0.6-0.8 g / cm 3 , monofilament fiber diameter: 7-13μm, short cut length: 2-5mm.

[0020] The elastomer is a linear TPE thermoplastic elastomer with a styrene content of 22%, a volatile content of ≤0.7, an oil filling rate of 0%, and a melt flow rate of 3 (190° C., 2.16 kg).

[0021] The compatibilizer is a maleic anhydride grafted TPE with a density of 0.89-0.94 g / cm3 , hardness (Shore D) 20-40, melt flow rate 2.6 (190°C, 2.16kg), resilience: 3-10%, maleic anhydride grafting rate: 0.5-1.0%.

[0022] The antioxidant is a mixture of a phosphite antioxidant and a hindered phenol antioxidant in a ratio of 1:1 (by weight), wherein the phosphite antioxidant may be tetrakis(2,4-di-tert-butylphenol)-4,4'-biphenyl diphosphite, CAS: 119345-01-6; tris[2.4-di-tert-butylphenyl]phosphite, CAS No. 31570-04-4; 3,9-bis(2,4-dicumylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, CAS No. 154862-43-8; and the hindered phenol antioxidant may be N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, CAS No.23128-74-7; triethylene glycol ether-di(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate, CAS No.36443-68-2; pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, CAS No.6683-19-8, etc.; a mixture of cuprous halide and potassium halide; at least one of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, CAS No.10081-67-1, etc.

[0023] The hindered phenol antioxidant of the present invention is preferably N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, and the phosphite antioxidant is preferably 3,9-bis(2,4-dicumylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane.

[0024] The processing aid is one or more of silicone powder, silicone masterbatch, PETS, rice bran wax, montan wax, polyethylene wax, oxidized polyethylene wax, calcium stearate and the like.

[0025] Rice bran wax is preferred in the present invention.

[0026] The masterbatch can be one or more of carbon black, zinc sulfide, iron oxide, etc. according to the color requirements, with a toner content of 20-90%, and a carrier of PA6, EBA or lubricant.

[0027] The high-damping, high-strength, good-appearance polyamide composite material and its preparation method are characterized by:

[0028] The following steps are involved:

[0029] (1) The moisture content of polyamide resin and polyamide resin PA6I is not higher than 2000ppm;

[0030] (2) Weighing various dried raw materials according to the formula ratio; mixing the polyamide resin, elastomer, compatibilizer, antioxidant, processing aid, and masterbatch uniformly by a high-speed mixer and setting aside; weighing the semi-aromatic polyamide PA6I and glass fiber according to the ratio and setting aside;

[0031] (3) The resin and additive mixture is added through the main feed port of a twin-screw extruder, and glass fiber is added through the side feed port after compaction by the twin-screw extruder. After melt extrusion, granulation, drying and other processes, the polyamide composite material is obtained.

[0032] The high-damping, high-strength and good-appearance polyamide composite material prepared by the present invention has important application prospects in the vibration reduction and suspension systems around automobile engines, and provides a new material solution for improving the NVH performance of automobiles.

[0033] The present invention has developed a high-damping, high-strength, good-appearance polyamide composite material, which has the advantage of having a higher damping temperature range. By utilizing the good fluidity and high glass transition temperature (Tg) of PA6I, PA6I can preferentially flow to the surface of the workpiece during injection molding, thereby encapsulating the lagging glass fiber inside the workpiece. At the same time, the higher glass transition temperature (Tg) and amorphous polymer properties of PA6I increase the Tg of the modified polyamide composite material, and the damping effect of the material can be maximized near Tg, achieving a higher damping effect at the operating temperature (80-120°C) of the engine peripheral vibration reduction component area. In addition, the special vibration reduction unit used is a compound of linear TPE and maleic anhydride grafted TPE, which improves the compatibility of the material while further improving the damping effect of the material, providing a new material solution for replacing steel components with plastic in the vibration reduction area around the engine of current fuel vehicles and hybrid vehicles, and improving the NVH performance of the entire vehicle. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the product appearance diagram of Example 1;

[0035] Figure 2 This is the product appearance diagram of Comparative Example 1;

[0036] Figure 3 This is the product appearance diagram of Comparative Example 3. DETAILED DESCRIPTION

[0037] In order to make the technical problems to be solved by the present invention and the practical effects clearer, the present invention will be further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0038] The embodiments and comparative examples of the present invention use the following materials, but are not limited to the following materials:

[0039] Polyamide resin PA66, PA6, PA56, trade name EP1106, produced by Huafeng, trade name YH400, produced by Yuehua, PA56 produced by Cathay;

[0040] Semi-aromatic polyamide resin PA6I, commercially available;

[0041] Glass fiber, trade name ECS301HP-3, produced by Chongqing International Composite Materials Co., Ltd.;

[0042] Elastomer, linear TPE, produced by Yuehua;

[0043] Compatibilizer, maleic anhydride grafted TPE type thermoplastic elastomer, commercially available;

[0044] Processing aid, commercially available under the trade name R05;

[0045] Antioxidant 1010 (SI Group), hindered phenol antioxidant, commercially available;

[0046] Antioxidant 9228, phosphite antioxidant, commercially available;

[0047] Black masterbatch, PA6-2015, commercially available;

[0048] Preparation methods of Examples 1-3 and Comparative Examples 1-5:

[0049] Preparation method of damping noise reduction polyamide composition:

[0050] (1) The moisture content of polyamide resin and polyamide resin PA6I is not higher than 2000ppm;

[0051] (2) Weighing various dried raw materials according to the formula ratio; mixing the polyamide resin, elastomer, compatibilizer, antioxidant, processing aid, and masterbatch uniformly by a high-speed mixer and setting aside; weighing the semi-aromatic polyamide PA6I and glass fiber according to the ratio and setting aside;

[0052] (3) The resin and additive mixture is added through the main feed port of a twin-screw extruder, and glass fiber is added through the side feed port after compaction by the twin-screw extruder. After melt extrusion, granulation, drying and other processes, the polyamide composite material is obtained.

[0053] Preparation of test specimens of damping and noise reduction polyamide composition:

[0054] The above materials were dried in a forced air drying oven at 120° C. for 4 hours and then injection molded into standard specimens at an injection molding temperature of 240-300° C. The prepared mechanical properties specimens were conditioned in a standard laboratory environment (23° C., 50% RH) for 24 hours before testing.

[0055] Test methods for each performance index:

[0056] Tensile properties: According to ISO 527 method, sample size: 170*10*4mm, test speed 5mm / min.

[0057] Bending properties: According to ISO 178 method, sample size: 80*10*4mm, test speed 2mm / min.

[0058] Notched impact performance: According to ISO 179 method, sample size: 80*10*4mm.

[0059] Damping factor: DMA three-point bending test was used with a frequency of 1 Hz, a temperature range of -30 to 120°C, a heating rate of 3°C / min, a strain of 0.05%, and the tanδ and Tg of the test material to obtain a tanδ peak value and Tg of 60-100°C.

[0060] Table 1: Composition and properties of polyamide composite materials of Examples 1-3 and Comparative Examples 1-5

[0061]

[0062]

[0063] By comparing Examples 1, 2, and 3 in Table 1 with Comparative Example 1, it is shown that the addition of linear TPE can effectively improve the damping factor tanδ, and the addition of compatibilizer maleic anhydride grafted TPE can further improve the damping performance of the material and inhibit the serious decline in mechanical properties. However, with the increase in the content of linear TPE, the strength and modulus of the material will still decrease significantly, while the toughness will increase; Comparison between Example 1 and Comparative Examples 2 and 3 shows that the addition of PA6I significantly improves the appearance of the injection molded plate, and Tg is also significantly increased. In addition, PA6I further improves the damping factor tanδ; Comparison between Example 1 and Comparative Examples 2, 4, and 5 shows that the combined effect of linear TPE and PA6I can also play the same effect in PA6 and PA56 resins, and can become a universal solution in polyamide materials. The high-damping, high-strength, good-appearance polyamide composite material prepared by the present invention has important application prospects in the vibration reduction and suspension systems around automobile engines, and provides a new material solution for improving automobile NVH performance.

[0064] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A high damping, high strength and good appearance polyamide composite material, characterized by: It is composed of the following raw materials in percentage by weight: Polyamide resin 30-60%; Semi-aromatic polyamide resin PA6I: 1-15%; Glass fiber: 30-70%; Elastomer: 1-15%; Compatibilizer: 1-3%; Antioxidant: 0-1%; Processing aids: 0-2%; Masterbatch: 0-1%.

2. The high-damping, high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The polyamide resin may be one or more of PA6, PA56, PA66, PA6 / 66, and PA66 / 6.

3. The high-damping, high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The semi-aromatic polyamide resin PA6I is an amorphous polyamide resin, and has a melting point and a glass transition temperature (Tg) of 120-130° C. and a melt flow rate (MFR) of 25-40 g / 10 min.

4. The high-damping, high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The glass fiber is one or more of E glass fiber, S glass fiber and A glass fiber.

5. The high-damping, high-strength and good-appearance polyamide composite material according to claim 4, characterized in that: The glass fiber is E glass fiber, with alkali content less than 0.8%, water content less than 0.05%, and bulk density of 0.6-0.8 g / cm 3 , monofilament fiber diameter: 7-13μm, short cut length: 2-5mm.

6. The high-damping, high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The elastomer is a linear TPE thermoplastic elastomer with a styrene content of 22%, a volatile content of ≤0.7, an oil filling rate of 0%, and a melt flow rate of 3.

7. The high-damping, high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The compatibilizer is a maleic anhydride grafted TPE with a density of 0.89-0.94 g / cm 3 , Shore D hardness is 20-40, melt flow rate is 2.6, resilience: 3-10%, maleic anhydride grafting rate: 0.5-1.0%.

8. The high-damping, high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The antioxidant is a mixture of a phosphite antioxidant and a hindered phenol antioxidant in a weight ratio of 1:1, wherein the phosphite antioxidant can be tetrakis(2,4-di-tert-butylphenol)-4,4'-biphenyl diphosphite, CAS: 119345-01-6; tris[2.4-di-tert-butylphenyl]phosphite, CAS No. 31570-04-4; 3,9-bis(2,4-dicumylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, CAS No. 154862-43-8; the hindered phenol antioxidant can be: N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, CAS No.23128-74-7; triethylene glycol ether-di(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate, CAS No.36443-68-2; pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, CAS No.6683-19-8, etc.; a mixture of cuprous halide and potassium halide; at least one of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, CAS No.10081-67-1.

9. The high-damping, high-strength and good-appearance polyamide composite material according to claim 8, characterized in that: The hindered phenol antioxidant is N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, and the phosphite antioxidant is 3,9-bis(2,4-dicumylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane.

10. The high-damping, high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The processing aid is one or more of silicone powder, silicone masterbatch, PETS, rice bran wax, montan wax, polyethylene wax, oxidized polyethylene wax, calcium stearate and the like.

11. The high-damping, high-strength and good-appearance polyamide composite material according to claim 10, characterized in that: The processing aid is preferably rice bran wax of the present invention.

12. The high-damping, high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The masterbatch can be one or more of carbon black, zinc sulfide, and iron oxide according to color requirements, with a toner content of 20-90%, and a carrier of PA6, EBA or a lubricant.

13. The method for preparing the high-damping, high-strength and good-appearance polyamide composite material according to any one of claims 1 to 12, characterized in that: The following steps are involved: (1) The moisture content of polyamide resin and polyamide resin PA6I is not higher than 2000ppm; (2) Weighing various dried raw materials according to the formula ratio; mixing the polyamide resin, elastomer, compatibilizer, antioxidant, processing aid, and masterbatch uniformly by a high-speed mixer and setting aside; weighing the semi-aromatic polyamide PA6I and glass fiber according to the ratio and setting aside; (3) The resin and additive mixture is added through the main feed port of a twin-screw extruder, and glass fiber is added through the side feed port after compaction by the twin-screw extruder. After melt extrusion, granulation, drying and other processes, the polyamide composite material is obtained.

14. The high-damping, high-strength and good-appearance polyamide composite material according to any one of claims 1 to 12, characterized in that: High damping, high strength and good appearance polyamide composite materials are used in vibration reduction and suspension systems around automobile engines.

Citation Information

Patent Citations

  • High-damping long-chain nylon ABS (Acrylonitrile Butadiene Styrene) alloy material and preparation method thereof

    CN115926364A

  • Glass fiber-reinforced polyamide 66 and semi-aromatic nylon composite material for vehicular structural member and preparation method

    CN106700535A

  • High-damping heat-aging-resistant polyamide composition and preparation method thereof

    CN111253734A

  • Glass fiber reinforced nylon composite material as well as preparation method and application thereof

    CN114921091A